2020
DOI: 10.1016/j.tree.2020.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Analogies for a No-Analog World: Tackling Uncertainties in Reintroduction Planning

Abstract: Species reintroductions involve considerable uncertainty, especially in highly altered landscapes. Developing robust historical, geographic, and taxonomic analogies can help reduce this uncertainty, and integrating these analogies can enable conservationists to better assess the suitability of reintroduction sites. We illustrate this approach using the example of the California grizzly, an iconic species proposed for reintroduction despite significant knowledge gaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Concentration dependence was incorporated into the models using data from [35]. End member values were defined using mean time and tissue-corrected 13 C and 15 N isotope values and associated standard deviations for food groups from each region and time period. Mixing models were run with an uninformative prior, three Markov chain Monte Carlo (MCMC) chains of 300 000 draws, and a burn in of 200 000 draws.…”
Section: (G) Spatio-temporal and Dietary Analysesmentioning
confidence: 99%
See 3 more Smart Citations
“…Concentration dependence was incorporated into the models using data from [35]. End member values were defined using mean time and tissue-corrected 13 C and 15 N isotope values and associated standard deviations for food groups from each region and time period. Mixing models were run with an uninformative prior, three Markov chain Monte Carlo (MCMC) chains of 300 000 draws, and a burn in of 200 000 draws.…”
Section: (G) Spatio-temporal and Dietary Analysesmentioning
confidence: 99%
“…Two specimens from the pre-1542 time bin, both from the Central Coast region, had values consistent with marine resource use (δ 15 N = 14 and 18‰, δ 13 C = −17 and −12.8‰; hereafter called 'marine bears'), but marine resource use was not apparent in any of the grizzlies collected during the post-1542 time bin, despite a larger sample size with strong coastal representation (see also electronic supplementary material, figure S2). Grizzly bivariate stable isotope signatures differed between the time bins (MRPP, p ca 0.003 and p < 0.0001 for analyses including or excluding the two marine bears), owing to an increase in grizzly δ 15 N values (Mann-Whitney U-tests with and without marine bears: δ 15 N p < 0.005 and < 0.0001, respectively; δ 13 C p > 0.30 and > 0.07), suggesting an increase in carnivory through time and a consistent reliance on terrestrial food. Similarly, we found that δ 15 N values increased through time whether marine bears were included or not (δ 15 N values versus years before present (ybp), Spearman's ρ's = + 0.41 and +0.50, p ca 0.002 and 0.0002, respectively) and that δ 13 C values (Suess corrected) and years before present were related when marine bears were excluded (ρ = +0.34, p = 0.012), but not when marine bears were included (ρ = + 0.26, p = 0.06).…”
Section: (B) the California Grizzly's Isotopic Menumentioning
confidence: 99%
See 2 more Smart Citations
“…Reintroduction biology, however, is beset with tensions between traditional actions to restore historical habitat and more novel approaches that incorporate environmental change (Corlett, 2016;Taylor et al, 2017). For example, historical distributions typically drive decisions on where to direct translocation efforts, yet these baselines decline in relevancy in rapidly changing ecosystems (Forbes et al, 2020). A more innovative approach to translocations is to target habitats that are becoming more appropriate for some species, even in the absence of evidence for historical occupancy (Peterson St-Laurent et al, 2021).Yosemite National Park (Yosemite) and the broader Sierra Nevada Mountains encompass elevational gradients and biodiversity patterns that can facilitate shifting species ranges and, therefore, accommodate conservation translocations (Singer,…”
mentioning
confidence: 99%